2019
DOI: 10.1039/c9cp04032c
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM simulations of organic phosphorus adsorption at the diaspore–water interface

Abstract: The available phosphorus for plants is mainly affected by the strong binding of phosphates to soil mineral surfaces. Here, we have investigated the molecular mechanisms for this binding process at the surface–water interface by QM/MM MD simulations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 54 publications
11
35
3
Order By: Relevance
“…In addition, Persson et al [43] suggested a dominant M motif for monomethyl phosphate (MMP; CH 3 -H 2 PO 4 ) adsorption onto goethite. However, similar to our previous studies [47,48], we find that GP forms stable and strong B or BB motifs, see Figure 2a. In addition, Lü et al [80] suggested that molecules with similar binding mechanism like GP such as glucose 6-phosphate and adenosine mono/triphosphates form nonprotonated bidentate complexes within first ten minutes after mixing.…”
Section: Discussion Of Goethite-gp-water Interactionssupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, Persson et al [43] suggested a dominant M motif for monomethyl phosphate (MMP; CH 3 -H 2 PO 4 ) adsorption onto goethite. However, similar to our previous studies [47,48], we find that GP forms stable and strong B or BB motifs, see Figure 2a. In addition, Lü et al [80] suggested that molecules with similar binding mechanism like GP such as glucose 6-phosphate and adenosine mono/triphosphates form nonprotonated bidentate complexes within first ten minutes after mixing.…”
Section: Discussion Of Goethite-gp-water Interactionssupporting
confidence: 92%
“…Molecular Dynamics (MD) simulations are employed to sample the equilibrium dynamics including reactive events. As the phosphate interaction at goethite-water interface involve proton transfer events and covalent bond changes [46][47][48], using the QM/MM MD technique is mandatory. Specifically, the electron density cut-off for the auxiliary plane wave basis set is chosen to be 500 Ry with SCF convergence threshold of 10 −4 Hartree.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations